THE INFLUENCE OF FINANCIAL TECHNOLOGY, E-COMMERCE, ENVIRONMENTAL SECURITY, CAPITAL, AND LABOR ON THE DEVELOPMENT OF MSMES IN MEDAN CITY - Miftahul Jannah Hutasoit; Badaruddin Badaruddin; Tengku Irmayani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of Financial Technology, E-Commerce, Environmental Security, Capital, and Labor on the Development of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. The research method used was a quantitative approach with regression analysis to examine the relationships between variables. The results show that Financial Technology, Environmental Security, and Labor have a positive and significant influence on MSME Development in Medan City. This indicates that the use of financial technology, a safe environment, and the availability of an adequate workforce can encourage MSME growth. Conversely, the variables E-Commerce and Capital did not significantly influence MSME Development, indicating that the use of online platforms and the availability of capital are not yet fully determining factors in improving MSME performance in Medan City. These findings are expected to be considered by MSME actors and policymakers in optimizing factors that support the development of the MSME sector in the region.